The 100 Most Cited Papers in Radiotherapy or Chemoradiotherapy for Cervical Cancer: 1990–2020 - Wang, Weiping; Liu, Xiaoliang; Wang, Dunhuang; Ren, Kang; Zhou, Yuncan; Zhou, Ziqi; Qiu, Jie; Zhang, Fuquan; Hu, Ke (Frontiers in Oncology, 2021)
Objective: To analyze the 100 most cited papers in radiotherapy or chemoradiotherapy for cervical cancer. Methods: The 100 most cited papers in radiotherapy or chemoradiotherapy between 1990 and 2020 were identified with Thompson Reuters Web of Science citation indexing on August 24, 2020. The publication years, source titles, countries/regions, total citations, and average citations per year were extracted from the Web of Science. The research type and research domain were classified by the authors. Results: These 100 papers were cited a total of 28714 times, and the median number of citations was 169.5 (ranging from 116 to 1700 times). The most cited paper was “Concurrent cisplatin-based radiotherapy and chemotherapy for locally advanced cervical cancer” by Rose et al, with a total citation of 1700 times. The International Journal of Radiation Oncology Biology Physics (40 papers), Radiotherapy and Oncology (14 papers) and the Journal of Clinical Oncology (12 papers) published the largest number of papers. The USA (47 papers), Austria (18 papers), Canada (13 papers) and England (13 papers) contributed the largest number of papers. Image-guided adaptive brachytherapy (IGABT) had the largest number of papers (25 papers). Concurrent chemotherapy was the most cited research domain, with 10663 total citations and 592.4 citations per paper. Conclusion: In the present study, we conducted a bibliometric analysis of the 100 most cited papers in radiotherapy or concurrent chemoradiotherapy for cervical cancer in the past 30 years. IGABT and concurrent chemotherapy were the most cited research domains.